2001
DOI: 10.1159/000047836
|View full text |Cite
|
Sign up to set email alerts
|

Motoneurons of the Lateral and Medial Rectus Extraocular Muscles in Squirrel Monkey and Cat

Abstract: The goal of this study was to examine and compare the number and size of motoneurons in the cat and squirrel monkey abducens nucleus. We also examined medial rectus muscle motoneuron compartmentalization in the squirrel monkey oculomotor nucleus and compared those cells to abducens nucleus motoneurons. Retrograde labeling of the motoneurons, using cholera toxin conjugate of horseradish peroxidase (CTHRP) injected into cat and monkey lateral or medial rectus muscles, was observed after 24 h. The CTHRP was histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…8a,b, compare neurons in B and C). The mean diameter of the MR A-group and B-group motoneurons are 22.0 m (SD ϭ 2.7; n ϭ 170) compared with 18.1 m (SD ϭ 2.6; n ϭ 27) for the C-group (Bü ttner-Ennever and Akert, 1981;McClung et al, 2001). An injection into the intermediate portion of MR, avoiding the central endplate zone (Expt.…”
Section: Oculomotor Nucleusmentioning
confidence: 95%
“…8a,b, compare neurons in B and C). The mean diameter of the MR A-group and B-group motoneurons are 22.0 m (SD ϭ 2.7; n ϭ 170) compared with 18.1 m (SD ϭ 2.6; n ϭ 27) for the C-group (Bü ttner-Ennever and Akert, 1981;McClung et al, 2001). An injection into the intermediate portion of MR, avoiding the central endplate zone (Expt.…”
Section: Oculomotor Nucleusmentioning
confidence: 95%
“…1A). In agreement with other studies, we found that the A and B group motoneurons were nearly the same size, but the C group neurons were significantly smaller (A motoneurons: 356.3 Ϯ 94 m 2 mean area Ϯ SD, n ϭ 58; B motoneurons: 386.7 Ϯ 118.7 m 2 , n ϭ 54; C group: 221.5 Ϯ 58 m 2 , n ϭ 57; P ϭ 0.001, SPSS 7.5 two-tailed Student's t-test; Bü ttner-Ennever and Akert, 1981;McClung et al, 2001). …”
Section: Nontwitch Motoneuron Subgroups In the Oculomotor Nucleusmentioning
confidence: 99%
“…The most prominent group of MIF motoneurons is formed by those of the IR and MR, termed the C group . It lies at the dorsomedial border of nIII and can be identified in several species, such as cat, lesser galago, marmoset, and macaque (Büttner‐Ennever and Akert, ; Büttner‐Ennever et al, ; Clarke et al, ; McClung et al, ; Spencer and Porter, ; Sun and May, ). Recent tract‐tracing studies in monkey indicated that the peripheral MIF motoneuron groups including the C group may also contain the cell bodies of palisade endings (Lienbacher et al, ; Zimmermann et al, ).…”
mentioning
confidence: 99%